Determination of dissolved organic carbon and total dissolved nitrogen in seawater using High Temperature Combustion Analysis - Halewood, Elisa; Opalk, Keri; Custals, Lillian; Carey, Maverick; Hansell, Dennis A.; Carlson, Craig A. (Frontiers in Marine Science, 2022)
This document describes best practices for analysis of dissolved organic matter (dissolved organic carbon and total dissolved nitrogen) in seawater samples. Included are SOPs for sample collection and storage, details for laboratory analysis using high temperature combustion analysis on Shimadzu TOC analyzers, and suggestions for best practices in quality control and quality assurance. Although written specifically for GO-SHIP oceanographic community practices, many aspects of sample collection and processing are relevant to DOM determination across oceanic regimes and this document aims to provide updated methodology to the wider marine community.